2017
DOI: 10.1111/cbdd.12951
|View full text |Cite
|
Sign up to set email alerts
|

Structural improvement of new thiazolidinones compounds with antinociceptive activity in experimental chemotherapy‐induced painful neuropathy

Abstract: Chemotherapy-induced neuropathy is a disabling pain condition resulting from chemotherapy for cancers. Up to now, no drug is available to cure chemotherapy-induced neuropathy. In the present study, we describe the structural design, synthesis, chemical and pharmacological characterization of 15 thiazolidinones, a class of potential analgesic compounds. The synthesis of new thiazolidinones was achieved by using the thiazolidinone heterocyclic as main structural pharmacophoric group and varying the substituents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…OA is a chronic progressive disease with complicated mechanisms that include inflammation, periarticular bone response, and cartilage degradation [ 18 20 ]. To date, the available pain treatments are limited in their efficacy and known to possess associated toxicities, none of which halts disease progression or regenerates damaged cartilage or bone [ 21 ]. Thus, current therapeutic strategies seek to ameliorate pain, offer chondroprotective or regenerative capability, and increase mobility, thereby representing the critically unmet needs.…”
Section: Introductionmentioning
confidence: 99%
“…OA is a chronic progressive disease with complicated mechanisms that include inflammation, periarticular bone response, and cartilage degradation [ 18 20 ]. To date, the available pain treatments are limited in their efficacy and known to possess associated toxicities, none of which halts disease progression or regenerates damaged cartilage or bone [ 21 ]. Thus, current therapeutic strategies seek to ameliorate pain, offer chondroprotective or regenerative capability, and increase mobility, thereby representing the critically unmet needs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, if the response of animals to a compound is tested in both the LDB and the open field, an increase in LDB-light in the absence of a change in locomotor activity in the open field would suggest that the investigated compound has a specific anxiolytic effect, but no sedative effect, which is highly desirable in anxiolytics especially from a translational perspective (82)(83)(84). Upon literature review, we have found as many records in which the open field was performed as a test of locomotor activity (80,81,85,86), as we have found records in which it was performed as a test of anxiety (87)(88)(89)(90). Here, we identify an issue with the continuation of such tests as long-held standards that may not be appropriate, due to the researcher's degree of freedom in the interpretation of the test's meaning (91,92).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the present study aimed to assess whether treatment with gabapentin can affect IENFs and CGRP density in the mice’ hind paws at a time point that significantly confers an analgesic effect in an experimental TIPN mice model that closely mimics the course of peripheral neuropathy in human patients. To the best of our knowledge, this is the first study showing the decreased density of CGRP and PGP 9.5-positive nerve fibers innervating the paw skin in the TIPN model and their increase after 21 days of gabapentin treatment, justifying gabapentin use as a gold standard reference compound in the preclinical TIPN mouse model [ 31 , 32 , 33 ], as found in a randomized, placebo-controlled, clinical trial [ 34 ]. Present findings refine the TIPN mice model and further support the claim that skin biopsy with quantification of the density of IENF and CGRP, using generally agreed-upon counting rules, is a reliable, efficient, and objective technique, complementary to analgesia, to assess gabapentin effects on peripheral neuropathy both in patients and in animal models of peripheral neuropathy.…”
Section: Introductionmentioning
confidence: 99%